Assessment of the quality of mobile telecommunications services - Martins, Catarina Cecílio (2017)
Over the past decades, the telecommunications sector has grown both in terms of revenues, both in terms of number of clients, which in turn has meant that the demand for the quality of services provided by mobile network operators increased. Given the above, this thesis aims to assess how clients perceive the perceived quality of the mobile network operator service through a quality measurement tool adapted to the respective sector (SERVPERF). With regard to methodology, an online questionnaire was applied based on SERVPERF instrument developed by Cronin Jr. and Taylor (1992), adding some items due to the peculiarity of mobile telecommunications services. In order to process the data obtained, the Statistical Package for Social Sciences ("SPSS") version 22 was used exclusively, which allowed for various statistical calculations. With regard to the results, there is a general positive perception of the quality of mobile telecommunications services, highlighting the Communication dimension, but only with a very little significant difference regarding the Tariff dimension. In addition, and after having performed the Principal Component Analysis ("PCA") the initial eight dimensions became only three, namely: Service Provider, Accessibility and Comunication and Tangibility. Lastly, some recommendations were proposed to improve the perceived quality of service being studied, regarding a proximity policy, the implementation of the service, the disclosure / provision of information and the facilities.